Widespread occurrence of anomalous C-band backscatter signals in arid environments caused by subsurface scattering - Wagner, Wolfgang; Lindorfer, Roland; Melzer, Thomas; Hahn, Sebastian; Bauer-Marschallinger, Bernhard; Morrison, Keith; Calvet, Jean-Christophe; Hobbs, Stephen; Quast, Raphael; Greimeister-Pfeil, Isabella; Vreugdenhil, Mariette (Elsevier, 2022)
Backscatter measured by scatterometers and Synthetic Aperture Radars is sensitive to the dielectric properties of the soil and normally increases with increasing soil moisture content. However, when the soil is dry, the radar waves penetrate deeper into the soil, potentially sensing subsurface scatterers such as near-surface rocks and stones. In this paper we propose an exponential model to describe the impact of such subsurface scatterers on C-Band backscatter measurements acquired by the Advanced Scatterometer (ASCAT) on board of the METOP satellites. The model predicts an increase of the subsurface scattering contributions with decreasing soil wetness that may counteract the signal from the soil surface. This may cause anomalous backscatter signals that deteriorate soil moisture retrievals from ASCAT. We test whether this new model is able to explain ASCAT observations better than a bare soil backscatter model without a subsurface scattering term, using k-fold cross validation and the Bayesian Information Criterion for model selection. We find that arid landscapes with Leptosols and Arenosols represent ideal environmental conditions for the occurrence of subsurface scattering. Nonetheless, subsurface scattering may also become important in more humid environments during dry spells. We conclude that subsurface scattering is a widespread phenomenon that (i) needs to be accounted for in active microwave soil moisture retrievals and (ii) has a potential for soil mapping, particularly in arid and semi-arid environments.
Keywords: ASCAT; Radar backscatter; Scattering; Deserts; Arid environments